2012
DOI: 10.1590/s0103-64402012000100005
|View full text |Cite
|
Sign up to set email alerts
|

Effect of high-concentrated bleaching agents on the bond strength at dentin/resin interface and flexural strength of dentin

Abstract: This study evaluated the effect of bleaching agents on bond strength at the dentin/resin interface and the flexural strength of dentin. Forty maxillary canines were selected for the study. In the shear strength test, 40 slabs of intracoronary dentin (5 x 5 mm) obtained from buccal surfaces of the crowns were included in acrylic resin. In the flexural strength test, 40 dentin bars (8 x 2 x 2 mm) were obtained from the roots. The 40 hemi-sections of the lingual surface were prepared for scanning electron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 22 publications
0
20
1
Order By: Relevance
“…Flexural strength test usually follow the ISO 4049 standard that state specimen with 25 x 2 x 2 mm. The dimensions used in the present study are different from the ISO, however also observed in prior studies [20][21][22] . Other dimensions are also used in the literature, such at Vieira et al 22 (2012) and Firoozmand and Pagani 23 (2009).…”
Section: Discussionmentioning
confidence: 67%
“…Flexural strength test usually follow the ISO 4049 standard that state specimen with 25 x 2 x 2 mm. The dimensions used in the present study are different from the ISO, however also observed in prior studies [20][21][22] . Other dimensions are also used in the literature, such at Vieira et al 22 (2012) and Firoozmand and Pagani 23 (2009).…”
Section: Discussionmentioning
confidence: 67%
“…This hypothesis supports the observation of absence of hybrid layer and resin tags and decreased MTBS observed in this study. Vieira and colleagues also reported the absence of resin tags and discontinuity areas at the interface when 38% H 2 O 2 was applied on intact dentin. Changes in Ca to P ratio, reduction in the organic components of dentin by protein oxidation, and hydroxyl radical‐mediated damage to organic components of dentin have also been proposed to be responsible for reduced MTBS.…”
Section: Discussionmentioning
confidence: 99%
“…Due to its strong oxidizing effect, ozone might have negative consequences on resin-tooth adhesion, since oxygen is a well-known polymerization inhibitor 9 . It has been demonstrated that oxygen and other oxidant agents (such as bleaching agents) have a negative influence on dental adhesives bond strength 29 .…”
Section: Introductionmentioning
confidence: 99%